2013
DOI: 10.1080/0020739x.2013.770087
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical literacy in undergraduates: role of gender, emotional intelligence and emotional self-efficacy

Abstract: This empirical study explores the roles that Emotional Intelligence (EI) and Emotional Self-Efficacy (ESE) play in undergraduates' mathematical literacy, and the influence of EI and ESE on students' attitudes towards and beliefs about mathematics. A convenience sample of 93 female and 82 male first-year undergraduates completed a test of mathematical literacy, followed by an online survey designed to measure the students' EI, ESE and factors associated with mathematical literacy. Analysis of the data revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 27 publications
1
21
0
4
Order By: Relevance
“…AEI predicts academic success, even after personality and academic intelligence are statistically controlled (Lyons & Schneider, 2005). The AEI facet of emotion management is particularly important in determining whether students cope with adaptation to specific and general university stressors (MacCann et al, 2011;Tariq et al, 2013). TEI also predicts academic achievement of university students (e. These findings indicate that undergraduate students with greater EI use more effective coping strategies for academic and social situations (Austin, Saklofske, & Mastoras, 2010;Saklofske, Austin, Galloway, & Davidson, 2007).…”
Section: Adjustment To University: the Importance Of Emotional Intellmentioning
confidence: 92%
See 1 more Smart Citation
“…AEI predicts academic success, even after personality and academic intelligence are statistically controlled (Lyons & Schneider, 2005). The AEI facet of emotion management is particularly important in determining whether students cope with adaptation to specific and general university stressors (MacCann et al, 2011;Tariq et al, 2013). TEI also predicts academic achievement of university students (e. These findings indicate that undergraduate students with greater EI use more effective coping strategies for academic and social situations (Austin, Saklofske, & Mastoras, 2010;Saklofske, Austin, Galloway, & Davidson, 2007).…”
Section: Adjustment To University: the Importance Of Emotional Intellmentioning
confidence: 92%
“…TEI also predicts academic achievement of university students (e. These findings indicate that undergraduate students with greater EI use more effective coping strategies for academic and social situations (Austin, Saklofske, & Mastoras, 2010;Saklofske, Austin, Galloway, & Davidson, 2007). Skills in managing emotion are most consistently implicated in these associations (Davis & Humphrey, 2012;Tariq et al 2013;MacCann, Fogarty, Zeidner, and Roberts, 2011).…”
Section: Adjustment To University: the Importance Of Emotional Intellmentioning
confidence: 95%
“…In the context of Pakistan, Tariq, Qualter, Roberts, Appleby and Barnes (2013) found that female learners with a high emotional intelligence demonstrated superior confidence and lower mathematical anxiety. Similarly, Chaudhry, Ali,…”
Section: Introductionmentioning
confidence: 99%
“…A UK study found that male students are more confident in quantitative skills than their female counterparts. (Tariq, Qualter, Roberts, Appleby, & Barnes, 2012). Other studies concluded that females prefer teamwork and gain more educational benefits than males (Curran, Sharpe, Forristall, & Flynn, 2008;Wainer, Bryant, & Strasser, 2001).…”
Section: Demographic Differences In Perceptionsmentioning
confidence: 92%